TRIM21/Ro52 - Roles in Innate Immunity and Autoimmune Disease - Jones, Esther L.; Laidlaw, Stephen M.; Dustin, Lynn B. (Frontiers in Immunology, 2021)
TRIM21 (Ro52/SSA1) is an E3 ubiquitin ligase that plays key roles in immune host defence, signal transduction, and possibly cell cycle regulation. It is also an autoantibody target in Sjögren’s syndrome, systemic lupus erythematosus, and other rheumatic autoimmune diseases. Here, we summarise the structure and function of this enzyme, its roles in innate immunity, adaptive immunity and cellular homeostasis, the pathogenesis of autoimmunity against TRIM21, and the potential impacts of autoantibodies to this intracellular protein.